Barriers and enablers in the use of respite interventions by caregivers of people with dementia: an integrative review - Marie-Conception Leocadie; Marie-Hélène Roy; Monique Rothan-Tondeur (BMC, 2018)
Abstract Background Due to the increase in the number of people with dementia, relatives often provide in-home care. This care constitutes a cornerstone of the healthcare system, and maintaining these caregivers' well-being is therefore of paramount importance. Although respite interventions are generally considered an effective support system, they tend to be underutilized. The aim of this integrative literature review is to highlight the factors that promote and impede the use of respite interventions. Methods Searches were conducted on the PubMed and CINAHL databases for studies of respite interventions from 1980 to 2016, and they yielded 51 articles of relevance. Results Analysis of these articles revealed modifiable and immutable factors that influence the use of respite. The most cited topic categories in the literature were attributes of respite services and workload managed by caregivers, which is characterized by the onset of burden. Conclusion The factors promoting or impeding the use of respite interventions identified by our analysis highlight the need to adapt respite service attributes and use caregivers' skills to foster the partnership between healthcare teams and caregivers and to ensure the accompanying dyad's quality and safety.